PRODUÇÃO DE LAMBARI-DO-RABO-AMARELO (Astyanax altiparanae), ALFACE CRESPA (Lactuca sativa var. Crispa) E ALFACE AMERICANA (Lactuca sativa L.) EM AQUAPONIA - ROCHA, Rayssa Albuquerque; WANDERLEY, Alysson Martins; BARROS, Adriana; FERRAZ, André Luiz Julien; CAMPOS, Cristiane Meldau (ANAIS DO ENIC, 2022)
-